204k views
1 vote
Wiwsiiiisieitiitittiti

User Huy T
by
5.0k points

1 Answer

4 votes

Using the definition for the average, and naming each reasut as:

Average = 73

First score = 76

Second score = x-5

Third score= x

Write the equation


\begin{gathered} 73=(76+(x-5)+(x))/(3) \\ 73=(71+2x)/(3) \\ 219=71+2x \\ 148=2x \\ x=(148)/(2) \\ x=74 \end{gathered}

The second score is 69 and the third score is 74.

User Hevlastka
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.